Validity of a Centrifuge-Based Method for Determining the Water Retention Curve of Growing Media - Hadi Hamaaziz Muhammed; Lisa Schumm; Ruediger Anlauf; Tobias Reineke; Diemo Daum (Horticulturae)
The water retention curve (WRC) determines important properties of growing media with respect to water dynamics. However, the standard laboratory determination is time-consuming and laborious. The objectives of this study were (i) to test the practical applicability of the centrifuge method as a quick test for a wide range of growing media, (ii) to compare a simple substitution method to describe the bulk density of growing media with the results of the standard method, and (iii) to give a recommendation under which conditions (the mean weighted diameter of the substrate particles is 5 mm or less) the centrifuge quick test could serve as a replacement for the standard DIN method. Water content vs. water suction values determined for the whole range of the water retention curve with the standard method, and centrifugation results were compared and evaluated by correlation analyses. The results showed good agreement (R2 ≥ 0.98) between the centrifuge and DIN methods, with the effect of material compression in the centrifuge method resulting in a statistically significant correlation between compression and bias at low pF stages. This, however, did not lead to significant deviations between the method’s results at low pF stages (<pF 2.0). The method’s rapidity (2 days vs. up to 8.5 days) and correlation with standard methods highlight its potential for practical applications. Limitations, such as compression effects, were noted, emphasizing the need for careful interpretation. Overall, the centrifuge method provided a valuable research and substrate development tool. This study contributes to refining measurement techniques in growth substrates, encouraging ongoing research in water dynamics in growing media.